Influence Competency, Education and Training Against Performance Through Development Carier at The Distrik Navigasi Kelas I Makassar - Randa, Esra; Ruslan, Muhlis; Abubakar, Herminawaty (Indonesian Journal of Business and Management, 2018)
The purpose of this study is to study, analyze and interpret, (1)The influence of competence on the performance (2) the influence of education on carier development (3) the effect of training on employee performance (4)The influence of competence on carier development (5) the effect of training on carieer development (6) the influence of carier development on employee performance (7) The influence of education on employee performance through carier (8) the influence of competence, training education on employee performance through carier development at Distrik Navigasi Kelas I Makassar. The research method used is sampling method take research sample counted 71 people from civil servant at Distrik Navigasi Kelas I Makassar as respondent, data collection techniques by using questionnaires to determine the effect of independent variables on the dependent variabele either simultaneously or partially using path analysis. The results of the research indicate that (1) Competence has nott direct effect on carieer development (2) education has a positive and significant effect on career development (3) Training has a positive and significant impact on carieer development (4) Competence has a positive and significant effect on employee performance (5)Education does not directly affects the performance of employees (6) Training has not effect and not significant on employee performance (7)Carieer development has a direct effect on employee performance (8)Competence, education and training affect the performance of employees through carieer development